2010
DOI: 10.1177/1557988310376959
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Symptoms of Psychological Ill Health Among Adult Male Offenders

Abstract: The current study investigated the relationship between personality and symptoms of psychological ill health in adult male offenders. Male offenders (N = 161) housed at two medium-high-risk institutions completed the Ten Item Personality Inventory and the Symptom Checklist Outpatient Rating Scale. Emotional stability emerged as the strongest individual predictor of psychological ill health and predicted each of the subscales measured (somatization, obsessive-compulsive, interpersonal sensitivity, depression, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Different studies have indicated a correlation between neuroticism (the personality dimension of emotional stability) and health-related quality of life (Buneviciute, Staniute, Brozaitiene, Girdler, & Bunevicius, 2013;McCann, 2014). Costa and McCrae (1990) found a strong correlation between the Neuroticism factor and indices of Borderline, Paranoid, Schizoid, and Schizotypal personality disorders, while Brewer (2011) found that the Neuroticism factor is the only one of the five personality factors that successfully predicted the entire scale for Psychopathology among offenders. Accordingly, McCann (2014) held that individuals with high scores of neuroticism are in an at-risk group for different psychopathologies and for psychological distress in general.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have indicated a correlation between neuroticism (the personality dimension of emotional stability) and health-related quality of life (Buneviciute, Staniute, Brozaitiene, Girdler, & Bunevicius, 2013;McCann, 2014). Costa and McCrae (1990) found a strong correlation between the Neuroticism factor and indices of Borderline, Paranoid, Schizoid, and Schizotypal personality disorders, while Brewer (2011) found that the Neuroticism factor is the only one of the five personality factors that successfully predicted the entire scale for Psychopathology among offenders. Accordingly, McCann (2014) held that individuals with high scores of neuroticism are in an at-risk group for different psychopathologies and for psychological distress in general.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain the health of male nursing students, their physical, social, and psychological well-being should be considered. If they have low self-esteem or a negative self-image during their studies, they may experience mental distress and subsequently fall physically ill (Brewer, 2011;Janzen & Kelly, 2012). The aim of this study was to enhance the psychological well-being of male nursing students by giving voice to this minority group, so as to achieve the goal of holistic care for all.…”
mentioning
confidence: 99%